Batik Ratu Banten in an Ethnomathematics Lens: Historical Value and Mathematical Value - Vidya Ayuningtyas; Yuke Andriani; Sulistiawati; Destri Astrianingsih; Anggi Rahmani (Department of Mathematics Education, Faculty of Teacher Training and Education, Universitas Islam Malang, 2025)
Mathematics is a basic science that is very necessary in daily activities, and contributes to the advancement of science and technology. In addition to the functional aspect, mathematics also has an aesthetic side that can be combined with cultural elements in a work of batik art, namely Batik Ratu Banten. This approach involving mathematical and cultural concepts is known as ethnomathematics, which can be used as a source in contextual mathematics learning that is interesting for students by connecting abstract mathematical concepts with real cultural artifacts. However, learning in schools in Banten has not fully integrated cultural elements into mathematics learning. Therefore, this study aims to examine Batik Ratu Banten from historical and mathematical values. The research method is qualitative with an ethnographic approach. Research data were obtained from interviews, observations, and documentation, with the subject data source being the Batik Ratu Banten UMKM actors. The data received is analyzed to dissect and clarify the philosophy and describe batik motifs using a geometric approach, using data reduction techniques, data presentation, and concluding so that research conclusions are obtained. The results of the study concluded that Batik Ratu Banten not only contains historical elements of Banten, but also mathematical values. Behind the beautiful carvings of the artwork of Batik Ratu Banten, there are mathematical values in the form of the concept of number patterns, the concept of circles in the material of flat shapes, the concept of lines and angles, and the concept of reflection, translation, and rotation in the material of transformation geometry. This finding shows that Batik Ratu Banten can function as a source of learning mathematics in understanding the material to be more contextual and meaningful.